TOPOLOGY OPTIMIZATION DESIGN OF HIGH SPEED EMU GEARBOX - GAO Yang; QUE HongBo; BIAN Xiang; WEI YuZhou (Jixie qiangdu)
As the core component of high-speed EMU bogie, gearbox should meet the requirements of lightweight and high reliability in order to ensure the safety and comfort of vehicle operation. Taking the gearbox of a domestic high-speed EMU as the research object, the existing problems of the gearbox are analyzed by finite element method, then using the topology optimization technology to improve the design of the box structure. The results of finite element analysis show that the stiffness and strength of the gearbox meet the requirements under various working conditions. But it’s natural frequency is close to the main vibration frequency of wheel shaft system, which may cause resonance that leading to noise and box cracks. According to this characteristic, a topology optimization scheme is proposed to increase the natural frequency of the box. Verified by calculation and modal test, the natural frequency of the gearbox after topology optimization is raised to an interval that avoiding the main vibration frequency of wheel shaft system and reducing the possibility of resonance. The research in this paper provides theoretical and data support for the design of high-speed EMU gearbox with good static and dynamic characteristics.